If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6xy + 8yz + -7xz + -6xy = 0 Reorder the terms: 6xy + -6xy + -7xz + 8yz = 0 Combine like terms: 6xy + -6xy = 0 0 + -7xz + 8yz = 0 -7xz + 8yz = 0 Solving -7xz + 8yz = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8yz' to each side of the equation. -7xz + 8yz + -8yz = 0 + -8yz Combine like terms: 8yz + -8yz = 0 -7xz + 0 = 0 + -8yz -7xz = 0 + -8yz Remove the zero: -7xz = -8yz Divide each side by '-7z'. x = 1.142857143y Simplifying x = 1.142857143y
| 3+4[x+5]=27 | | 5+9[x+7]=122 | | -32=23m+13-8m | | 3X^2-25X=-2X^2-9X-12 | | 2x^2-rx=20 | | 6[m-3]+4=28 | | -7-p=-6p+8 | | -1+x=7-7x^2 | | 4x-9=10x-3 | | 8+2[p+1]=30 | | 6v+9+3v=-18+2v+9 | | 3.6t-7.2=34.4+8.8t | | -4(r+7)=-69 | | N+12=-8 | | f(x)=(-5-11)(-5+1) | | -18-3x=-48 | | 8+10+2c=-10-5c | | 5(-t-3)=60 | | -5(r+3)=-64 | | 2.5x-2.8=-31.6+9.7x | | -9-26+x=-46 | | 8-3x=21x-49 | | 4x+6y-26=32 | | 5b^2=60b-175 | | 5[a+3]=3a+31 | | 2x^2+x=x^2-20 | | 2d=a-c | | F(x)=9x-25 | | 44=-5-3(-4x+4) | | sin(30t)=0.5 | | 6[e+5]=9e-6 | | 59+11x=169 |